Enzymatic hydrolysis of chicken feet for bioactive peptides: method validation and protein quantification - Rusydan, Azka Muhammad; Rahayu, Adelia Ragil; Rohmah, Siti Dzurriatur; Firdausia, Rizqa Salsabila (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2024)
Background: Stunting affects 21.5% of Indonesian children under five, primarily due to chronic nutritional deficiencies. Chicken feet, underutilized poultry byproducts rich in protein, represent potential sources of bioactive peptides for nutritional interventions. Objective: This study evaluated two enzymatic hydrolysis methods for producing bioactive peptides from chicken feet and validated analytical methods for protein quantification. Methods: Chicken feet were hydrolyzed using bromelain and sequential papain-alcalase treatments. Soluble proteins were quantified using the Biuret assay. Analytical methods were validated for accuracy, precision, and linearity according to ICH guidelines. Results: The analytical method demonstrated satisfactory performance with accuracy values of 98-102%, RSD values below 2%, and linearity (R² = 0.9977) across the 3-11 mg/mL range. Bromelain treatment significantly increased soluble protein content to 24.39 ± 0.65 mg/mL, representing a 1.71-fold increase compared to the non-hydrolyzed control (14.24 ± 0.20 mg/mL, p < 0.001). Conversely, papain-alcalase treatment decreased soluble protein content to 10.92 ± 0.05 mg/mL, likely due to excessive peptide degradation into free amino acids undetectable by the Biuret assay. Conclusion: Bromelain hydrolysis demonstrated superior protein solubilization efficiency compared to papain-alcalase treatment. These preliminary findings suggest bromelain’s potential for converting chicken feet into functional ingredients, though further peptide characterization and bioactivity assessment are required for nutritional applications.